Processes for phosphorus removal from iron ore - a review - Pereira,Antônio Clareti (2015)
This paper aims at reviewing literature on the occurrence of phosphorus in iron ores from the mines around the world. The review extends to the phosphorus removal processes of this mineral to meet the specifications of the steel industry. Phosphorus is a contaminant that can be hard to remove, especially when one does not know its mode of occurrence in the ores. Phosphorus can be removed from iron ore by very different routes of treatment. The genesis of the reserve, the mineralogy, the cost and sustainability define the technol ogy to be applied. The articles surveyed cite removal by physical processes (flotation and selective agglomeration), chemical (leaching), thermal and bioleaching processes. Removal results of above 90% and less than 0.05% residual phosphorus are noticed, which is the maximum value required in most of the products generated in the processing of iron ore.